Oral and craniofacial manifestations of mucopolysaccharidoses - Leal, Fernanda (2020)
Mucopolysaccharidoses (MPS) are a group of inherited metabolic disorders caused by the deficiency of lysosomal enzymes necessary for the degradation of glycosaminoglycans (GAGs). Non-degraded GAGs accumulate inside the lysosomes and compromise cell function in different tissues and organs. This accumulation causes progressive and multisystemic damage, leading to a wide spectrum of clinical manifestations, including oral and craniofacial manifestations. This work aims, therefore, to conduct a literature review that promotes specific knowledge regarding the oral and craniofacial manifestations of MPS. The results converged to a variability of alterations, among them facial dysmorphism, macroglossia, lingual protrusion, anterior open bite, dental caries, gingival inflammation, enamel hypoplasia, taurodontism, condylar hypoplasia and presence of dentigerouscysts. Preventive and interceptive actions in oral health are used as a means of improving oral hygiene and reducing oral problems. Finally, there is a need for improvement in comprehensive care for patients with MPS.